Tracheal Calcification Following Warfarin Administration: A Case Report - Sara Salarian; Sogol Asgari; Faranak Behnaz (Archives of Anesthesia and Critical Care, 2023)
Warfarin ought to be utilized for an extended duration in individuals with a predisposition to thromboembolism, such as those with atrial fibrillation or aortic valve replacement. While the primary complication of long-term warfarin usage is the potential for bleeding, there are also infrequent complications like vascular and tracheal calcification. We present a case of a patient who experienced diffuse tracheal calcification as a result of long-term warfarin usage.